Indirect Taxation of Financial Services - Vidar Christiansen (Center for Economic Studies and ifo Institute (CESifo), 2017)
An important question is whether VAT exemption of financial services is a desirable property or whether it is justified only due to practical and administrative necessity. This paper singles out a number of financial services for discussion of this issue in a context allowing for other taxes and other preexisting distortions. It discusses taxation of intermediation that facilitates savings and borrowing, payment services and currency exchange. It also elaborates on the distortionary effects of taxing intermediate goods due to VAT exemption with focus on exports and consumer prices.
Keywords: H20; H21; H22; 330; financial services; indirect taxation; value added tax; VAT exemptions